1992
DOI: 10.2135/cropsci1992.0011183x003200050033x
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod, Temperature, and the Interval from Sowing to Tassel Initiation in Diverse Cultivars of Maize

Abstract: Photoperiod and temperature influence the time from sowing to tassel initiation (TI) in maize (Zea mays L.), with appreciable genetic differences in relative sensitivity to these factors. Three experiments were run to examine these photothermal responses and genetic differences within 12 diverse cultivars chosen to represent germplasm adapted to temperate, tropical highland, tropical lowland, and subtropical environments. Photoperiod influenced the rate of progress toward TI in all cultivars (P < 0.05), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 0 publications
3
57
0
3
Order By: Relevance
“…Genetically, different allele frequency-dependent models could be invoked to hypothesize on the dynamics of change in this latter phase of selection (for example, with respect to increasing variance: Goodnight, 1988), and ongoing analysis using genotype data will hopefully permit such inference. However, at the level of the whole genotype (individual), variation in temperature-dependent flowering time has been noted for maize across the range of temperatures that occurred in the environments of the present study (Ellis et al, 1992), and analysis of environmental variables associated with gEI in this study revealed adaptation to low temperature as a relevant factor (Figure 6).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Genetically, different allele frequency-dependent models could be invoked to hypothesize on the dynamics of change in this latter phase of selection (for example, with respect to increasing variance: Goodnight, 1988), and ongoing analysis using genotype data will hopefully permit such inference. However, at the level of the whole genotype (individual), variation in temperature-dependent flowering time has been noted for maize across the range of temperatures that occurred in the environments of the present study (Ellis et al, 1992), and analysis of environmental variables associated with gEI in this study revealed adaptation to low temperature as a relevant factor (Figure 6).…”
Section: Discussionmentioning
confidence: 50%
“…Other mechanisms such as response to temperature, which varies among maize germplasm sources (Ellis et al, 1992), are also thought to be important. Thus, photoperiod insensitivity is required but not sufficient to alleviate the spectrum of symptoms associated with the poor adaptation of tropical germplasm to temperate environments.…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature stress is documented to have detrimental effects on plant growth (Wamngton and Kanemíisu, 1983) and events involved in the growth and develclpment of reproductive organs, such as tassel initiation and time of flowering (Ellis et al, 1992), pollination and fertilization (Dupuis and Dumas, 1990), pollen sterility (Saini and Aspinall, 1982). and rate and duration of endosperm cell division (Jones et (a]., 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic variation was small or nonexistent for maize planted on the same date , Birch et al 1998a), but may be larger at high temperatures (Ellis et al 1992). Birch et al (1998a) found no differences in phyllochron among temperate and tropically-adapted maize hybrids grown at Gatton, southeastern Queensland, Australia.…”
Section: Introductionmentioning
confidence: 92%